2014
DOI: 10.4236/anp.2014.34020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Tantalum Hydride Using Mechanical Milling and Its Characterization by XRD, SEM, and TGA

Abstract: In this paper, we report the results obtained from different phases of metal hydrides. The synthesis and characterization of tantalum hydrides were obtained "in situ" during mechanical milling. Elemental Ta with purity of 99.8% was used in this investigation to obtain the hydrides. A highenergy ball milling technique was utilized to prepare hydrogenated phases. Ta hydrides and oxides were formed as function of milling process time. Milling times of 5, 10 and 20 hours were programmed, and the ball-to-powder wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Figure shows a comparison of X-ray diffraction (XRD) data based on reported experiments and our calculations. The XRD patterns of Ta 2 H (TaH 0.5 ) reported by Iturbe-García et al and TaH 0.2 given by Simonović et al are shown as bold black curves in Figure a,b, respectively. Our calculations based on C 222 (Ta 2 H) and C 2 (Ta 5 H) agree well with the experimentally reported XRD patterns (see the red curves in Figure ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Figure shows a comparison of X-ray diffraction (XRD) data based on reported experiments and our calculations. The XRD patterns of Ta 2 H (TaH 0.5 ) reported by Iturbe-García et al and TaH 0.2 given by Simonović et al are shown as bold black curves in Figure a,b, respectively. Our calculations based on C 222 (Ta 2 H) and C 2 (Ta 5 H) agree well with the experimentally reported XRD patterns (see the red curves in Figure ).…”
Section: Resultsmentioning
confidence: 91%
“…synthesized tantalum hydrides by utilizing a high-energy ball milling technique. Their XRD analysis demonstrated that Ta 2 H and TaH 0.5 were obtained after 20 h of milling . As far as we know, the superconductivity of Ta–H compounds and the compressed tantalum hydrides have been barely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of C is mainly due to the tape where Mg 2 Cu powders were placed for its analysis because it is made of this material and possibly from methanol used as control agent process. The presence of oxygen may be also due to methanol where the conditions were created into container during milling and solvent dissociation was realized in their components oxygen, carbon and hydrogen which was demostrated elsewere [29]. The oxygen may be reacted with magnesium in a too much small concentration such that the results of X-ray diffraction did not detect the corresponding oxide because the equipment sensitivity is less than 1%.…”
Section: Resultsmentioning
confidence: 99%